“Foreign” language aptitude predicts individual differences in native grammatical proficiency - Llompart Miquel; Dąbrowska Ewa (Linguistics)
Language aptitude is known to be a strong predictor of success in late second-language (L2) learning in instructional settings but is generally assumed to be irrelevant for native language (L1) acquisition. We investigated the relationship between language aptitude and L1 grammatical proficiency in the two studies reported here. Language aptitude was measured by means of a newly-developed test of grammatical sensitivity (Studies 1 and 2) and the Language Analysis subtest of the Pimsleur Language Aptitude Battery (Study 1), whereas grammatical proficiency was assessed by a grammaticality judgment task in Study 1 and a picture selection task in Study 2. The results of the two studies reveal a robust relationship between language aptitude and L1 grammatical proficiency that is remarkably consistent across different measures for both variables and appears to hold across the board for a variety of grammatical structures. These results fit well with the proposal that explicit learning may play an important role not only in adult L2 learning but also in L1 acquisition and raises questions about the validity of arguments for a fundamental difference between L1 and L2 acquisition based on the premise that only the latter is related to aptitude.